The Influence of Capital and Work Environment on The Performance of MSME Employees of Bogor Regency West Java Province by Covariable Marketing - Ismartaya (International Journal of Science, Technology & Management, 2021)
Micro, small and medium enterprises or MSMEs in Indonesia each year increase. The increasing number of MSMEs still needs to experience intensive assistance in order to achieve independent, resilient, and quality MSMEs. Employee performance is a form of employee achievement after going through various stages in the work process. Based on the observations, researchers showed that the performance of MSME employees in Babakan Madang subdistrict and Cisarua Sub-District of Bogor Regency was not optimal. This is allegedly due to being influenced by capital, work environment, and marketing. The formulation of problems in this research is whether the capital and work environment can affect the performance of employees directly or through the marketing of MSMEs in two sub-districts in Bogor Regency. This study aims to find out the influence of capital and work environment on employee performance with marketing co-operation on MSMEs Bogor Regency, this research uses the archework of The Posttest Only Control Group with marketing covariance. Data collection techniques use interviews and questionnaires, while sampling techniques use non probability sampling with a sample number of 72 people. The results showed that capital and work environment have a positive and significant effect on employee performance through marketing. This can be seen from the results of simple linear regression analysis, multiple linear regression, t test, determination coefficient test, sobel test and path analysis. Marketing as a moderator variable mediates between capital to employee performance that is partial mediation and marketing as moderator variables that mediate between the work environment and employee performance, both of which are full mediation.